Effective Control -in Depth- of the Arbitral Award: The Royal Football Club Seraing Judgment of the CJEU (C-600/23) - Gómez Jene, Miguel (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The CJEU judgment in the RFC Seraing case represents a further step in definingthe complex relationship between arbitration and EU law. Issued in the context of a case concerning the re-cognition in a Member State of a CAS award (sports arbitration, seated in Switzerland), the Court under-takes a broad analysis of the compatibility of that award with the EU legal order. It is very important to emphasize that this analysis is carried out applying certain fundamental rules of EU law: specificaly, the compatibility of arbitration with EU law is examined in light of the right to effective judicial protection as guaranteed by Articles 19 TEU and 47 of the Charter of Fundamental Rights of the European Union (CFR). On this basis, the CJEU requires an effective and in depth review of the foreign arbitral award at the recognition stage, rules on the effectiveness of the arbitration agreement, and limits the parties’ autonomy in defining interim relief The CJEU judgment is particularly significantfor Spanish courts. Firstly, because it corrects certain case law of the Constitutional Court, which failed at the time to appreciate the relevance of mandatory EU law in the context of setting aside arbitral awards. Secondly, because it imposes a model of effective review of arbitral awards, much more rigorous than that currently carried out by our High Courts of Justice due to an unfortunate line of Constitutional Court case law. Thirdly, because it allows us to anticipate the direction of the forthcoming decision in response to the timely and well-founded preliminary question referred by the High Court of Justice of Madrid. In fact, the judgment of the CJEU is so forceful that the preliminary question could well be withdrawn and the case resolved in accordance with it.